Integration of seasonal frequency domain electromagnetic surveys and geological data for assessing the integrity of earthen levee systems. The case study of the Panaro River (Northern Italy) - N. Bertone; E. Forte; G. Titti; R. Zambrini; P. Macini; A. Mocnik; S. Parodi; F. Pellegrini; M. Possamai; C. Staboli; M. Valente; L. Borgatti (Engineering Geology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The CHOPIn Study: a Multicenter Study on Cerebellar Hemorrhage and Outcome in Preterm Infants - V. Boswinkel; S. J. Steggerda; M. Fumagalli; A. Parodi; L. A. Ramenghi; F. Groenendaal; J. Dudink; M. N. Benders; R. Knol; L. S. de Vries; G. van Wezel-Meijler (The Cerebellum, 2019)

Temporal dynamics of algal epiphytes on Leathesia marina and Colpomenia sinuosa macrothalli (Phaeophyceae) - Ailen M. Poza; M. Cecilia Gauna; Juan F. Escobar; Elisa R. Parodi (Marine Biology Research, 2018)

Effects of storage time on the motility, mortality and calcium levels of Atlantic salmon Salmo salar spermatozoa - J. Parodi; G. Guerra; M. Cuevas; A. Ramírez‐Reveco; F. Romero (Journal of Fish Biology, 2017)
This study estimates spermatozoa mortality, morphology, motility and intracellular calcium levels in Atlantic salmon Salmo salar milt after prolonged storage. Milt samples were preserved at 4° C for 25 days and then evaluated for mortality. Motility remained high for the first 3 days and the mortality was low during the first 5 days of storage. A decrease of >50% in calcium content was observed after 5 days of storage. When spermatozoa were activated, calcium levels increased >200% in relative fluorescence units ( RFU ); this rate of increase was lost when the samples were stored for extended periods of time and was only partially manifested in a zero calcium solution. The results suggest that in vitro storage of S. salar spermatozoa at 4° C for a period of 3 days preserves motility and limits mortality to levels similar to those of fresh spermatozoa. This method also maintains intracellular calcium storage critical for spermatozoa performance.

American tegumentary leishmaniasis: T-cell differentiation profile of cutaneous and mucosal forms—co-infection with Trypanosoma cruzi - Cecilia Parodi; María F. García Bustos; Alejandra Barrio; Federico Ramos; Ana G. González Prieto; María C. Mora; Patricia Baré; Miguel A. Basombrío; María M. de Elizalde de Bracco (Medical Microbiology and Immunology, 2016)

Erratum to: Changes in Coastal Benthic Algae Succession Trajectories and Assemblages Under Contrasting Nutrient and Grazer Loads - A. Fricke; G. A. Kopprio; D. Alemany; M. Gastaldi; M. Narvarte; E. R. Parodi; R. J. Lara; F. Hidalgo; A. Martínez; E. A. Sar; O. Iribarne; P. Martinetto (Estuaries and Coasts, 2016)

Changes in Coastal Benthic Algae Succession Trajectories and Assemblages Under Contrasting Nutrient and Grazer Loads - A. Fricke; G. A. Kopprio; D. Alemany; M. Gastaldi; M. Narvarte; E. R. Parodi; R. J. Lara; F. Hidalgo; A. Martínez; E. A. Sar; O. Iribarne; P. Martinetto (Estuaries and Coasts, 2016)

Humic acid and moderate hypoxia alter oxidative and physiological parameters in different tissues of silver catfish (Rhamdia quelen) - Ana P. K. Riffel; Etiane M. H. Saccol; Isabela A. Finamor; Giovana M. Ourique; Luciane T. Gressler; Thaylise V. Parodi; Luis O. R. Goulart; Susana F. Llesuy; Bernardo Baldisserotto; Maria A. Pavanato (Journal of Comparative Physiology B, 2014)

Alterations in the enzymatic activity of plasma of guinea pigs infected with junn virus - F. Kierszenbaum; D. B. Budzko; A. S. Parodi (Archives of Virology, 1970)